Early occurrence of brief potentially ictal rhythmic discharges [B(I)RDs], and subsequent emergence of asymmetric extreme delta brush (EDB) in Anti-NMDA receptors encephalitis - Valmir Passareli; Lais Medeiros; Mateus Mistieri Simabukuro; Meire Baldocci; Sônia Maria Dozzi Brucki; Maria Sheila Guimarães Rocha (2015)
I)RDS], e surgimento posterior de assimétrico extremo "delta brush" (EDB) num caso